2016
DOI: 10.1016/j.appet.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

African-American and Hispanic children's beverage intake: Differences in associations with desire to drink, fathers' feeding practices, and weight concerns

Abstract: Relationships of African-American and Hispanic fathers’ feeding practices and weight concerns and preschoolers’ desire to drink with children’s beverage intake were examined, and associations between fathers’ feeding practices and children’s weight status were evaluated. Fathers’ (Hispanic n = 61, African-American n = 49) difficulty in child feeding, use of food to calm, use of food as reward, and concern about the child being under and overweight as well as their child’s desire to drink were assessed. Prescho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 58 publications
4
26
2
Order By: Relevance
“…51 In a study with low-income minority fathers of preschoolers, use of food as reward was associated with child’s intake of sugar-sweetened beverages in Latino children, but not in African-American children. 55 …”
Section: Discussionmentioning
confidence: 99%
“…51 In a study with low-income minority fathers of preschoolers, use of food as reward was associated with child’s intake of sugar-sweetened beverages in Latino children, but not in African-American children. 55 …”
Section: Discussionmentioning
confidence: 99%
“…Another study reported no association between fathers’ pressure to eat or restriction and their preschool age children’s weight status (Vollmer, Adamsons, Foster, & Mobley, 2015). More recently, one study examining the feeding practices of Latino and African American fathers of preschool age children reported no association between use of food as a reward and their children’s weight status (Lora, Hubbs-Tait, Ferris, & Wakefield, 2016). To gain a deeper understanding of the home food environment, more research is needed on the role of parent gender in these associations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, drinking engagement during mealtimes at 27 months of age predicted eating past satiation at 33 months of age. These findings are important, considering that the nature of children’s beverage drinking behaviors has been associated with increased intake of calories (Bonuck et al, 2010; Lora et al, 2016), yet such drinking behaviors have not been extensively considered with examined with respect to obesogenic eating behaviors such as EAH that may promote childhood obesity risk.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although drinking engagement may be a behavior that could lead to increased risk for obesity/overweight (e.g., through consuming more high-calorie beverages), to our knowledge, DD has not yet been directly evaluated in relation to obesogenic eating behaviors such as EAH that may signal risk for excessive weight gain during toddlerhood. Furthermore, although Lora and colleagues (2016) found that DD was associated with intake of sugar-sweetened beverages, this study was based on parent-report of child DD and intake of sugar-sweetened beverages. Toddler drinking engagement has also rarely been observationally assessed, despite the important potential benefits of using observational methods compared to maternal reports of child behaviors (Pesch & Lumeng 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation